Does conditional cash transfer deliver? The Indonesian evidence on PKH - Hudang, Adrianus Kabubu; Hariyanto, Tri; Handoyo, Rossanto Dwi (Business: Theory and Practice, 2024)
Social protection programs aim to secure individuals’ incomes from socioeconomic shocks and provide access to social services for developing human capital and alleviating poverty. In Indonesia, the Family Hope Program (PKH – Program Keluarga Harapan) is a social protection program that focuses on human capital development that requires children’s school enrollment and mothers and toddlers’ health as the conditions of cash transfers. This study seeks to analyze the effects of the PKH program on consumption expenditure, children’s educational attainment, and prenatal visits in Indonesia. We use the 2007 and 2014 IFLS (Indonesian Family Life Survey) survey data analyzed by the difference-in-difference (DID) method. The results demonstrate that PKH has a significantly positive effect on food consumption expenditure. However, PKH has insignificantly negative effects on children’s educational attainment and prenatal visits. The results suggest that the government monitors and ensures that the targeted recipients receive the program’s benefits. As such, the government can enhance the recipients’ awareness of the program’s benefits and ensure the equal availability of supporting infrastructure that enables households to utilize education and health facilities optimally.